2020
DOI: 10.3389/fneur.2020.01030
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Symptoms and Quality of Life in Patients With Adult-Onset Idiopathic Focal Dystonia and Essential Tremor

Abstract: Background: While idiopathic focal dystonia (IFD) and essential tremor (ET) have been considered pure movement disorders, they reportedly induce neuropsychiatric manifestations and may thus be more accurately described as network disorders. Methods: The present multi-center, cross-sectional, case-control study evaluated the severity of depression and anxiety with the Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI), respectively; the frequency of neuropsychiatric disorders with the Korean-Mini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In addition, it is well known that neurological disorders often result in increased disability and decreased quality of life that might make patients more prone to develop psychiatric conditions and consequently to seek formal medical care for both ET and psychiatric symptom management [47][48][49][50]. In this context, the onset of new ET symptoms might encourage patients to receive a new therapy for its management.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is well known that neurological disorders often result in increased disability and decreased quality of life that might make patients more prone to develop psychiatric conditions and consequently to seek formal medical care for both ET and psychiatric symptom management [47][48][49][50]. In this context, the onset of new ET symptoms might encourage patients to receive a new therapy for its management.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that 95.5% of patients with ET had at least 1 comorbidity, 79.7% had at least 3 comorbidities, and 56.9% JOURNAL OF HEALTH ECONOMICS AND OUTCOMES RESEARCH had at least 5 comorbidities. Multiple comorbidities are associated with poor health outcomes: decreased quality of life, 32,[35][36][37] increased psychological distress, 38 longer LOS, worse postoperative complications, and higher HCC and mortality. 24,[39][40][41] The interplay between multimorbidity and chronic disease is extremely important but receives inadequate attention in many chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…7,9 These symptoms may worsen over time and significantly impact a patient's quality of life and ability to perform activities of daily living. 2,[10][11][12] Medications used to treat ET can be moderately effective at reducing symptoms but do not treat the underlying disease. 13,14 It is estimated that only 30% to 50% of patients with ET respond to pharmacotherapy.…”
Section: Journal Of Health Economics and Outcomes Researchmentioning
confidence: 99%
“…In adult-onset patients, dystonia often remains focal, whereas in pediatric-onset patients, dystonia is more likely to progress from one body region to a generalized body involvement, which may pose burden on their development and daily life [2]. Apart from motor impairment, a sizable proportion of adult-onset dystonia patients have been shown to suffer from various non-motor symptoms, such as neuropsychiatric disturbance, sleep problems, sensory disorder and cognitive decline, some of them has been found to associate with the decreased quality of life [3][4][5].…”
Section: Introductionmentioning
confidence: 99%